How the closure of a U.S. tax loophole may affect investor portfolios - Christoph Frei; Liam Welsh (Journal of Risk and Financial Management, 2022)
In the United States, exchange-traded funds can defer capital gains taxes of their investors by taking advantage of a legal loophole. To quantify the impact of this tax loophole on investor portfolios, we study a rank-dependent expected utility model. We develop an approximation formula for the sensitivity of the optimal investment strategy with respect to changes in the expected asset returns. By applying this approximation formula, we are able to quantitatively estimate how much investor portfolios may change depending on the investment horizon if the tax loophole is closed.
Keywords: 650; capital gains tax; ETFs; mutual funds; portfolio allocation